Comparison of Immediate Induction (Within 6 Hours) Versus Late Induction (After 24 Hours) in Terms of Mean PROM to Delivery Interval in Females Presenting with Term PROM - Kanwal Firdos , Maliha Sadaf , Farzana Kazmi, Kanwal Firdos , Maliha Sadaf , Farzana Kazmi (Journal of Rawalpindi Medical College, 2018)
Background: To compare the immediate induction (within 06 hours) versus late induction (after 24 hours) in terms of mean pre-labour rupture of membranes (PROM) to delivery interval in females presenting with term PROM. Methods ; In this randomized controlled trial, 100 patients were enrolled per inclusion and exclusion criteria and randomly assigned to two groups. For Group A, induction of labor was immediately started with prostaglandin E2 vaginal tablet, whereas for Group B it was done 24 hours later. The PROM to delivery time for both groups was noted down, whether delivered vaginally or by caesarean section. The SPSS Version 17 was used to analyse the collected data. Quantitative variables like age, gestational age, parity and PROM to delivery interval were assessed by calculating mean and SD. Comparison of PROM to delivery interval between the two groups was done by using independent t test. p- Value <0.05 was considered significant. Results :The mean age of the patients included in the study was 28.40 ± 4.04 years. The means for gestational age and parity were 38.64 ± 1.15 weeks and 1.09 ± 1.00 respectively. The mean of PROM to delivery interval for Group A (immediate induction) was 13.36 ± 3.16 hours. The mean for patients in Group B (late induction) was 33.60 ± 4.06 hours (p-value=0.00) Conclusion :The mean time to delivery after PROM is shorter with immediate induction (within 6 hours) as compared to delayed induction (after 24 hours).